Keberagaman Masyarakat di Kota Metro Lampung - Albarra Sarbaini; Mohamad Erihadiana (Ath Thariq Jurnal Dakwah dan Komunikasi, 2021)
This study aims to determine how the diversity of people in the city of Metro Lampung related to pluralism and multiculturalism. This type of research is descriptive qualitative research, which is a research conducted systematically by collecting existing data in the field using data collection tools, namely, observation, interviews and documentation. Researchers found that people living in metro cities who have different livelihoods and professions including farmers, government employees, brick makers, entrepreneurs and other professions, are able to implement the values ​​of pluralism and multiculturalism which are closely related to humans, humanity and culture such as: learning to live in differences, building mutual trust, maintaining mutual understanding, upholding mutual respect, open thinking.